1997
DOI: 10.1159/000312888
|View full text |Cite
|
Sign up to set email alerts
|

Möglichkeit der Optimierung des ästhetischen und funktionellen Resultates von Defektheilungen nach Fazialisrekonstruktion und anderen fazialen Hyperkinesien durch operative Platysmaausschaltung

Abstract: UnerwÜnschte Platysmakontraktionen mit BeeintrÄchtigung der Unterlippenmimik kÖnnen sowohl im Rahmen von Synkinesien nach Fazialisrekonstruktionen als auch bei anderen fazialen Hyperkinesien auftreten. Um ihnen entgegenzuwirken, kann der Ramus colli nervi facialis durch selektive Neurektomie operativ ausgeschaltet werden. Wir berichten Über eine Patientin, bei der nach Akustikusneurinomoperation im Rahmen der mimischen Rehabilitation durch Hypoglossus-Fazialis-Anastomose (HFA) die selektive Neurektomie des Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Reduced facial movement after HFA may be caused by incomplete reinnervation, synkinesis or autoparalytic syndrome [24]. To optimize mimic rehabilitation after HFA, cross-facial nerve grafting [6] and selective peripheral neurectomy [9,25] have been introduced. In a study by Evans [26], 4 of 13 patients reviewed after HFA reported at least a slight limitation of their social life due to facial appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced facial movement after HFA may be caused by incomplete reinnervation, synkinesis or autoparalytic syndrome [24]. To optimize mimic rehabilitation after HFA, cross-facial nerve grafting [6] and selective peripheral neurectomy [9,25] have been introduced. In a study by Evans [26], 4 of 13 patients reviewed after HFA reported at least a slight limitation of their social life due to facial appearance.…”
Section: Discussionmentioning
confidence: 99%
“…after resection of tumours involving the cerebellopontine angle or the skull base, but also during parotid gland surgery to reach diversification in order to minimize synkinesis [1][2][3]. The result of mimic rehabilitation by HFA had been the subject of previous investigations also with regard to some modifications of this operative procedure [4][5][6][7][8][9]. Based upon a number of studies in which postoperative facial nerve function has commonly been evaluated by investigators using objective criteria such as nerve grading systems, there is general consensus that HFA may provide considerable facial reinnervation.…”
Section: Introductionmentioning
confidence: 99%
“…Hierzu kann man den Nervus auricularis magnus verwenden und das Interponat als End-zu-End-Anastomose peripher an den Nervus facialis anschlieûen und eine End-zu-Seit-Anstomose des zentralen Stumpfes des Interponates an den Nervus hypoglossus setzen. In eigenen Arbeiten [60,61] haben wir die zusätzliche Resektion des Ramus colli Nervi facialis zur Vermeidung von Platysma-Synkinesien während der operativen Anlage der Anastomose aufgezeigt. Hierdurch lassen sich störende Synkinesien des Platysmas gut vermeiden, da wegen der im Vergleich zur übrigen mimischen Muskulatur geringen ¹polytopen Innervationª dieses Muskels nur sehr wenige neu aussprossende Axone im Rahmen der Reinnervation das Platysma erreichen können.…”
Section: Hypoglossus-fazialis-anastomoseunclassified
“…Verantwortlich dafür ist die Vielzahl der Verzweigungen der peripheren Nervenäste in diesem Abschnitt der mimischen Muskulatur. Hier ist aber hervorzuheben, dass dieses für das Platysma so nicht gilt [60,61]. Dadurch, dass die Innervation des Platysmas fast ausschlieûlich über den Ramus colli nervi facialis erfolgt, kann eine hier erfolgte Neurektomie eine langandauernde Innervationsminderung bedingen.…”
Section: Fazialisdekompressionunclassified